Pemanfaatan Audio Visual dalam Pelayanan Konseling Keluarga Berencana (KB) - Israini Suriati; Andi Sitti Umrah; Nurafiantika; Juni Astuti Isnaini; Nurhaeni; Nurlisda; Fitri Nur Ima; Nailul Hikmah A; Andi Azzahra (JPM: Jurnal Pengabdian Masyarakat, 2024)
Family planning counseling services are key in providing accurate information and touching on psychosocial aspects of the family. This activity was carried out to explore the potential for using audio-visual media to increase the effectiveness of family planning counseling services. The family planning program determines the quality of the family, because this program can save women's lives and improve the health status of mothers, especially in preventing unwanted pregnancies, spacing births can reduce the risk of infant death. Contraception is used to maintain birth spacing. Thus, the use of contraception can also reduce the risk of maternal and infant death due to too close birth spacing. Implementation Method: By utilizing audio-visual media in counseling related to contraceptive material and various contraceptive methods, both hormonal and non-hormonal types. short-term contraceptive methods consisting of birth control pills and birth control injections, condoms. Then, long-term contraceptive methods consisting of intrauterine devices (IUD), implants, tubectomy and vasectomy. Activity Results: Couples of childbearing age understand more about the delivery of contraceptives and various types of contraceptives. As a result of delivering the material, there were around 67 couples of childbearing age who attended, there were around 30 couples who wanted to use PIL contraception for 1 and 3 months, then 10 couples who want to use contraceptive implants and IUDs. Conclusion: The use of audio visuals in family planning (KB) counseling services can provide many benefits, audio visuals are not only beneficial for counselors but also for clients.